2015
DOI: 10.1115/1.4029374
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturability Feedback and Model Correction for Additive Manufacturing

Abstract: M a n u fa c tu ra b ility F e e d b a c k and M o d e l C o rrectio n fo r A d d itiv e M a n u fa c tu rin g Additive manufacturing, or 3D printing, is the process o f building three-dimensional solid shapes by accumulating material laid out in sectional layers. Additive manufactur ing has been recognized fo r enabling production o f complex custom parts that are difficult to manufacture otherwise. However, the dependence on build orientation and physical limitations o f printing processes invariably lead t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 10 publications
0
41
0
Order By: Relevance
“…As shown in [15], assuming openings with disks allows a characterization of S ′ in terms of local size, defined as the distance of the boundary of S ′ to its medial axis. The complement of the opening O(S ′ , kX ) by a disk kX , k > 1 will outline the regions of S ′ with thin walls that are printable but are below the recommended thickness kX for the printed material (often learned by experimentation).…”
Section: Extruding As-manufactured Slicesmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in [15], assuming openings with disks allows a characterization of S ′ in terms of local size, defined as the distance of the boundary of S ′ to its medial axis. The complement of the opening O(S ′ , kX ) by a disk kX , k > 1 will outline the regions of S ′ with thin walls that are printable but are below the recommended thickness kX for the printed material (often learned by experimentation).…”
Section: Extruding As-manufactured Slicesmentioning
confidence: 99%
“…For a part S and a cutting tool F the maximal set of translations of the tool to avoid cutting into the part [15] is S c ⊖ F −1 . By the dual relationship between Minkowski sum and difference 1 this set of translations is (S ⊕ F −1 ) c , also realizable as the complement of the translational configuration space obstacle seen in robot motion planning.…”
Section: Remarkmentioning
confidence: 99%
“…Process limitations must be considered during the design/optimization stage as much as possible to avoid repeated prototyping and iterations until the optimized designs are manufacturable. Specifically, applying corrections to the geometry [9] or topology [11] of a solution after TO to make it manufacturable may sacrifice the achieved optimality.…”
Section: Optimal Design For Manufacturingmentioning
confidence: 99%
“…• binary-valued fields (Q i := {0, 1}), used to describe indicator functions of regions of interest within the design domain such as non-manufacturable features [7,8] or regions requiring design correction [9].…”
Section: Design and Performance Spacesmentioning
confidence: 99%
“…While the provided corrective actions improve the design significantly, it has been shown that the printability is not guaranteed. Nelaturi et al [35] use medial axis transformation together with techniques from mathematical morphology to construct a printability map and recommend design modifications. How- Fig.…”
Section: Manufacturability Analysis and Model Correctionmentioning
confidence: 99%